Mechanism of Coal Burst and Prevention Practice in Deep Asymmetric Isolated Coal Pillar: A Case Study from YaoQiao Coal Mine - Chengchun Xue; Anye Cao; Wenhao Guo; Songwei Wang; Yaoqi Liu; Zhiping Shen (Shock and Vibration)
Coal pillar bursts continue to be a severe dynamic hazard. Understanding its mechanism is of paramount importance and crucial in preventing and controlling its occurrence. The extreme roadway deformations from the asymmetric isolated coal pillars in the central mining district of YaoQiao Coal Mine have responded with frequent intense tremors, with risky isolated coal pillar bursts. The theoretical analysis, numerical simulation, and field measurements were done to research the impact of spatial overburden structure and stress distribution characteristics on the isolated coal pillar area, aiming to reveal the mechanism of coal pillar burst leading to the practice of prevention and control in the asymmetric isolated coal pillar area. The study shows that the overburden structure of the asymmetric is an asymmetric “T” structure in the strike-profile, and the stress in the coal pillar is mostly asymmetric “saddle-shaped” distribution, with the peak stress in the east side of the coal pillar, and the coal pillar is a “high stress serrated isolated coal pillar.” Numerical simulation results showed that the support pressure in the isolated coal pillar area on the strike profile was asymmetrically “saddle-shaped” distribution. The peak vertical stress in the coal pillar area continued to rise and gradually shifted to the mining district's deep part. As a result, the response of the roadway sides to the dynamic load disturbance was more pronounced. They developed a coal burst prevention and control program of deep-hole blasting in the roof of asymmetrical isolated coal pillar roof and unloading pressure from coal seam borehole. Monitored data confirmed that the stress concentration was influential in the roadway’s surrounding rock in the asymmetric isolated coal pillar area, circumventing coal pillar burst accidents. The research outcomes reference the prevention and control of coal bursts at isolated working faces of coal pillars under similar conditions.